Interrelationship of bottom fauna, fish and fisheries of Gobindsagar Reservoir, Himachal Pradesh - Koushal, D K (Indian Journal of Fisheries, 2011)
Benthic interaction among the communities with reference to fish was determinedin Gobindsagar, an impoundment across the river Sutlej. The material forinvestigation of intestinal contents of Cyprinus carpio and Labeo calbasu wasobtained from the three main ecological environments of the reservoir Theanalyses were combined with a study of benthos from the same environment.Conclusions drawn were that availability of benthos regulates the feedingbehaviour of Cyprinus carpio and Labeo calbasu. Under prevailing conditions boththese species have a selectivity for dipterans, especially larvae and pupae ofchironomids. The wide water level fluctuation affecting bathymetric distributionof benthos led to change in availability of benthos and consequently had an influenceon the trophic spectrum of the carp. Greater landings of Cyprinus carpio fromzone II and I were primarily due to more availability of benthos coupled with otherenvironmental factors.